2014
DOI: 10.1371/journal.pntd.0002761
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Rounds of Mass Drug Administration on the Association between Ocular Chlamydia trachomatis Infection and Follicular Trachoma in Preschool-Aged Children

Abstract: PurposeTo examine the relationship between ocular Chlamydia trachomatis infection and follicular trachoma (TF) in children prior to and following multiple rounds of annual mass drug administration (MDA) with azithromycin.Methodology/principal findingsThirty-two communities with endemic trachoma in Kongwa District, Tanzania, were offered annual MDA as part of a district-wide trachoma control program. Presence of ocular C. trachomatis infection and TF were assessed in 3,200 randomly sampled children aged five ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…This is consistent with earlier studies which found a stronger correlation as the underlying prevalence of infection increased (Ramadhani et al, 2016b ). However, in common with many other studies reporting the relationship between disease and infection, a minority (36%) of individuals with TF had detectable infection, probably due to the shorter duration of infection episodes relative to disease (Grassly et al, 2008 ; Burton et al, 2011a , c ; Lee et al, 2014 ). With increasing severity of both TF and TP scores, there was an increasing proportion with infection and increasing loads of infection.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This is consistent with earlier studies which found a stronger correlation as the underlying prevalence of infection increased (Ramadhani et al, 2016b ). However, in common with many other studies reporting the relationship between disease and infection, a minority (36%) of individuals with TF had detectable infection, probably due to the shorter duration of infection episodes relative to disease (Grassly et al, 2008 ; Burton et al, 2011a , c ; Lee et al, 2014 ). With increasing severity of both TF and TP scores, there was an increasing proportion with infection and increasing loads of infection.…”
Section: Discussionsupporting
confidence: 61%
“…Genes that were most strongly associated with active trachoma in the absence of C. trachomatis infection were enriched for pathways of leukocyte transendothelial migration, TNF receptors, MMP activation, collagen formation and assembly (Table 6 ). Active trachoma signs often persist after the clearance of C. trachomatis infection (Grassly et al, 2008 ; Burton et al, 2011a , c ; Lee et al, 2014 ) and inflammation is linked to progressive scarring (Ramadhani et al, 2016a ). We found that TP but not infection was associated with TS in the multivariable model (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, we would have had a rapid test of infection to decide which households to visit, but there was not one available at the time of the study. We have shown the correlation of trachoma and infection even in low prevalence settings which justified the use of this purposeful sampling approach [22]; 3) imprecise sampling area of the object being sampled. We tried to sample the area indicated by the caretaker, but this could be imprecise and subject to recall bias.…”
Section: Discussionmentioning
confidence: 93%
“…It is likely that repeated episodes of infection are reduced following MDA due to a decrease in circulating C. trachomatis and subsequently reduced transmission. Moreover, in populations undergoing MDA there is evidence that clinical signs of trachoma become less specific for C. trachomatis infection [ 36 , 37 ], suggesting that only the more severe phenotypes remain predictive of C. trachomatis infection. Azithromycin exhibits immunomodulatory effects that may be associated with reduced levels of inflammation [ 38 ], although at one year after a single dose this effect is unlikely to play a major role.…”
Section: Discussionmentioning
confidence: 99%